Développement D’un Stock De Semences (Seedstocks) De L’algue Rouge Gelidium Corneum (Gelidiaceae, Rhodophyta) - Chiheb, Houda; García-Jiménez, Pilar; Robaina, Rafael R.; Hassoun, Mustapha; Riadi, Hassane (European Scientific Journal, ESJ, 2018)
Gelidium corneum is a species of red algae notable for its commercial important as an agarophyte in Morocco. Several regions from the Moroccan Atlantic show that this alga is an endangered species due to the excessive tearing. Hence, the repopulation of these areas is necessary. The in vitro culture of the species was carried out in three media: enriched seawater medium (PES medium (Provasoli Enriched Seawater, Provasoli 1968)), medium with seawater (SW) and medium with artificial seawater, with the addition of polyamines (putrescine (put), spermidine (spd), and spermine (spr)) as a growth regulator in the three media. The results obtained are very significant, especially in PES medium with a growth rate of 95%. Rhizoid formation and attachment of explants have been noted, especially in PES + Put medium.